Abdominal Circumference as a Screening Measure for Type 2 Diabetes - Ghosh, JR; Bandyopadhyay, AR (Kathmandu University Medical Journal, 2014)
Background No comparative study has been conducted in India considering different anthropometrically derived adiposity measures to study the association with Type 2 Diabetes. Objective This study aims to examine the association of different adiposity measures and to find out the best adiposity measure in assessing Type 2 Diabetes. Method On 187 adult males aged 25-67 years, fasting and two hours postload glucose levels were assessed. Height, weight, hip circumference, and waist circumference at two anatomical sites, one at the level of the greatest anterior extension of the abdomen i.e. abdominal circumference and the other one at the narrowest part of the torso i.e. minimum waist circumference were measured. Waist hip ratio, body mass index, waist height ratio and conicity index were calculated subsequently. Results The prevalence of Type 2 Diabetes was 12.3%. Abdominal circumference revealed the highest odds ratio (OR 2.75; 95% CI 1.45 - 5.23) for Type 2 Diabetes, followed by waist height ratio (OR 1.86; 95% CI 1.05 - 3.32) and minimum waist circumference (OR 1.83; 95%CI 1.03 - 3.26). The area under the receiver operating characteristic curve of abdominal circumference was also larger (68%; 95%CI: 0.57 - 0.79) compared to other adiposity measures in assessing Type 2 Diabetes. Conclusion Waist circumference measured at the level of greatest anterior extension of the abdomen was the best central adiposity measurement in predicting and assessing Type 2 Diabetes. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10987 Kathmandu Univ Med J 2012;10(4):12-15